Reaction Pathways in Acrolein Oxidation over a Mixed‐Oxide Catalyst. Issue 22 (23rd October 2018) - Miller, Jacob H.; Bhan, Aditya
Abstract: A reaction network detailing the mechanistic origins of 17 C1 −C7 byproducts in acrolein oxidation over a vanadium molybdate mixed oxide catalyst doped with antimony and copper is proposed based on measurements of acrolein oxidation rates with co‐feeds of C1 −C7 organics formed as byproducts, acrylic acid 13 C isotopic tracer experiments, and probe molecule reactions. C1 and C2 products form via C−C bond scission of either the single or double C−C bond in acrolein and acrylic acid. C4 −C7 products form by addition of one or two acrolein or acrylic acid molecules to a C2 surface species coupled with decarbonylation or decarboxylation events. Two‐carbon ethyl and vinyl surface species and three‐carbon acrolein‐derived surface species are involved in all pathways that lead to byproduct formation; controlling the relative abundance and reactivity of such intermediates is integral to prescribing process conditions and material compositions for selective oxidation of acrolein. Abstract : Going into detail : A reaction network for acrolein oxidation detailing mechanistic origins of 17 C1 −C7 byproducts over a promoted MoVOx catalyst is proposed based on measurements of acrolein oxidation performed with various co‐processed species in a gas‐phase batch reactor. C1‐2 products form via scission of either the single or double bond in acrolein and acrylic acid. C4‐7 products form by addition of one or two acrolein or acrylic acid molecules to a C2 surface species coupled with decarbonylation or decarboxylation.